Decision Tree Method for Automation of Plant Sprinklers and Monitoring Based On Soil Moisture - Sri Siswanti; Muhammad Muchlasin; Muhammad Hasbi (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
Watering the plants is an important part of plant care, but due to our busy schedules, we frequently forget to do it. It can be caused by a number of variables, including the weather, in addition to human irresponsibility. The goal of this research is to develop a device that can automatically water plants and monitor plants based on soil moisture. Automatic sprinklers that use NodeMCU ESP8266 and Telegram bots employ the decision tree approach. The C 4.5 algorithm is used by the Decision Tree approach to choose the microcontroller's course of action. The value of various case studies utilized in this study is determined using algorithm C 4.5. The Arduino IDE, Fritzing, and Visual Studio Code were the tools used to design and produce this tool. Additionally, it configures Telegram bots using the Telegram universal bot library. The website setting for plant monitoring employs the native PHP language, but the configuration of the telegram bot uses the general telegraph bot library. The end result is an automatic plant sprinkler that operates based on the soil moisture value and activates the water pump when the soil moisture level drops below a threshold of 50%. When the soil moisture reading exceeds 75%, the water pump will then turn off. The outcomes of this investigation also comprise websites and Telegram bots for tracking soil moisture levels.